Enhanced Generation of Human Induced Pluripotent Stem Cells from Peripheral Blood and Using Their Mesoderm Differentiation Ability to Regenerate Infarcted Myocardium - Ju-Young Kim; Han-Mo Yang; Joo-Eun Lee; Mika Jeon; Sang-Bum Bang; Jihye You; Joonoh Kim; Jaewon Lee; Jin Hur; Hyo-Soo Kim (Stem Cells International)
Тhe most pressing issue in generating induced pluripotent stem cells (iPSCs) in clinical practice is the cell source. Compared to human dermal fibroblasts (HDFs), which have been widely used, human peripheral blood could be a more easily obtainable alternative. However, iPSCs generated from fresh peripheral blood require inconvenient specific methods including isolation. Recently, we succeeded in isolating and culturing human heart-derived circulating cells called circulating multipotent stem (CiMS) cells. Here, we investigated the generation efficiency of CiMS-derived iPSCs (CiMS-iPSCs) and tested their differentiation potential into mesodermal lineages and cardiovascular cells. We isolated and cultured CiMS cells from peripheral mononuclear cells with a high efficiency. Moreover, our method succeeded in reprogramming the CiMS cells and generating iPSCs with higher efficiency compared to when HDFs were used. Compared to HDF-iPSCs or human embryonic stem cells (hESCs), CiMS-iPSCs showed high differentiation potential into mesodermal lineage cells and subsequently into endothelial cells, vascular smooth muscle cells, and cardiomyocytes. Further, we checked the epigenetic status of each cell type. While methylation of the CpG site of the brachyury T promoter did not differ between cell types, the histone H3 lysine 4 trimethylation level in the brachyury T promoter region was enhanced in CiMS-iPSCs, compared to that in other cell types. In contrast, histone H3 lysine 9 acetylation was downregulated during the differentiation process of the CiMS-iPSCs. In the myocardial infarction model, the CiMS-iPSCs group showed more therapeutic potential in regenerating the myocardium than other cell types. Our study showed a new method to isolate human heart-derived stem cells from human peripheral blood and to generate iPSCs efficiently. Due to epigenetic memory, these CiMS-iPSCs easily differentiated into cardiovascular lineage cells, resulting in improved efficiency in vivo. These results suggest that our new method using CiMS cells has therapeutic potential in regenerative medicine using cell therapy.